The Main Principles of Adminisrative Licensing in Oil and Gas Sector of Norway - N. N. Shvets; M. Yu. Belyakova (Vestnik MGIMO-Universiteta)
The present article is dedicated to the analysis of administrative licensing procedure in Norwegian oil and gas sector. That is one of the most important mechanisms of state regulation in this area. The paper explores a wide range of reasons for choosing precisely this model of interaction between oil and gas companies and the state. The main aspects of the present administrative licensing system are highlighted in the article. Particular attention is paid to pre-qualification of oil and gas companies, participating in licensing rounds, especially to different criteria for choosing oil and gas companies that will operate on Norwegian Continental Shelf. Further conditions of their cooperation are provided. Moreover, the article refers to the role and the functions of state bodies in Norway that control and govern the licensing process - the Ministry of Petroleum and Energy and the Petroleum Directorate - and describes different types of licenses that exist in oil and gas sector of Norway. In conclusion the article shows numerous advantages of using the administrative licensing system in oil and gas sector, its impact on the economy of Norway and the possibility of its application in the oil and gas sector of Russia.